Advances in the prevalence and treatment of depression for adolescents: a review - Yin, Chunyu; Xu, Mengting; Zong, Zhiyuan (Frontiers in Pharmacology, 2025)
BackgroundDepression is a psychological condition in adolescents caused by various factors. Many serious consequences can be associated with depression, such as irritability, emotional instability, and suicide. Meanwhile, the incidence of depression and suicide among adolescents was also affected during the pandemic of COVID-19 in 2019. This phenomenon of adolescent depression should be drawn extensive concern by the community, which affects their physical and mental health.Main bodyThis review describes the epidemiology, high-risk factors, and treatment of adolescent depression. The onset of depression is probably attributable to preterm birth, growth environment, genetic. We also identify that the COVID-19 pandemic, initiated in late 2019,affects adolescent mental health. Antidepressants and psychotherapy are conventional treatments for depressive disorders. However, it is controversial whether antidepressants are as effective and safer as psychotherapy, and a combination of the two could provide more benefit to this population than antidepressants alone. We also summarize some antidepressants developed for novel targets. Improving the efficacy and safety of treatment to reduce the suicide rate among adolescents is the primary goal of clinical research. Existing treatment modalities and drugs are not sufficient to achieve clinical demands, so that new therapeutic targets will be promising for such patients.ConclusionA variety of factors can contribute to depression in adolescents. Adolescent depression should be mainly treated with non-pharmacological. A combination of guideline-recommended antidepressants should be used if uncontrolled with non-pharmacological, but adverse drug reactions and suicidal ideation should be closely monitored.